Epidermal nevus syndrome presenting as hypophosphatemic rickets: A case report of an uncommon association - Oranee Sanmaneechai (2018)
The epidermal nevus syndrome is a multisystem defect that includes epidermal nevi and cerebral and musculoskeletal abnormalities. We report the case of a 7-year-old Thai boy with hypophosphatemic rickets in a rare association with the epidermal nevus syndrome. The patient presented with growth retardation, bone pain, and generalized muscle weakness. Copyright © 2006 by Lippincott Williams & Wilkins.